2019
DOI: 10.17221/156/2018-pps
|View full text |Cite
|
Sign up to set email alerts
|

Meloidogyne hapla development on growing legume plants - Short Communication

Abstract: The legume genus lupine, pea, faba bean and common vetch were cultivated under natural conditions in pots filled with soil naturally infected with Meloidogyne hapla Chitwood, 1949. The nematode population density increased relevantly in the soil planted with the faba bean (cultivars (cvs.) Bobas, Amulet, Albus) and the pea cv. Lasso, in which numerous root galls and egg masses appeared. The narrow-leaved lupine (cvs. Karo, Zeus), yellow lupine (cvs. Parys, Lord) and white lupine (cv. Boros) cultivation decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The discrepancy in results may be explained by differences between the plant varieties used, test conditions and the type of material used (dry biomass vs. seed meal). The presented studies, however, showed a favourable effect of vetch seed meal applied in low (1% and 5%) doses, as this species is not a suitable host plant for the northern root-knot nematode (Dobosz & Krawczyk 2019). In addition to the positive im-pact on the growth and development, it has also been noticed that products made from plant tissues have a beneficial effect on the microbial richness of the soil (Jaffee 2006;Chauvin et al 2015;Chen et al 2019) and the diversity of bacterivorous and fungivorous nematode communities in the soil (Jaffee 2006;Renčo 2021).…”
Section: Discussionmentioning
confidence: 62%
“…The discrepancy in results may be explained by differences between the plant varieties used, test conditions and the type of material used (dry biomass vs. seed meal). The presented studies, however, showed a favourable effect of vetch seed meal applied in low (1% and 5%) doses, as this species is not a suitable host plant for the northern root-knot nematode (Dobosz & Krawczyk 2019). In addition to the positive im-pact on the growth and development, it has also been noticed that products made from plant tissues have a beneficial effect on the microbial richness of the soil (Jaffee 2006;Chauvin et al 2015;Chen et al 2019) and the diversity of bacterivorous and fungivorous nematode communities in the soil (Jaffee 2006;Renčo 2021).…”
Section: Discussionmentioning
confidence: 62%
“…Particular species of legumes have a different impact on the dynamics of M. hapla development in the soil [44]. The population dynamics of the northern root-knot nematode in the soil under annual and two-or three-year red clover and alfalfa precrop cultivation, involves the host suitability of each of those plant species to northern root-knot nematode, the precrop effects for succeeding crops and the timing of the sampling to determine the abundance of this nematode in soil towards assessing its damage potential to crops.…”
Section: Discussionmentioning
confidence: 99%
“…Thus resistance techniques should be targeted at limiting female populations since males are absent in most species [ 153 ], except in lesion nematodes, which assume a sexual mode of reproduction. The nematode complex can continue their unabated infection spree on available hosts and thrive for many years [ 61 , 63 , 155 , 156 , 157 ].…”
Section: Pea Rhizospheric Diseasesmentioning
confidence: 99%
“…For chemical control, fumigation with dichloropropene-based fungicides and non-volatile nematicides can provide a good control of these nematodes to improve pea yields [ 163 ]. Host resistance efforts, using infested fields and controlled pot experiments show promise [ 157 , 164 , 165 , 166 ]. However, for decades, the interest in plant parasitic nematodes has mainly focused on biological control and host–parasite interactions [ 154 ].…”
Section: Pea Rhizospheric Diseasesmentioning
confidence: 99%
See 1 more Smart Citation